A pesquisa sobre o fazer pesquisa: uma análise de citação da literatura periódica em Ciência da Informação - Freitas, Juliana Lazzarotto [UNESP]; Bufrem, Leilah Santiago [UNESP]; Oliveira, Ely Francina Tannuri de [UNESP]; Grácio, Maria Cláudia Cabrini [UNESP] (My University, 2014)
Introduction: This paper considers that information science (IS) literature covers a diversity of thematics with low emphasis on researches about conducting research. The study analyzes the scientific production of authors who investigate about research methodology in the information science (IS) literature, and the references used to lay the foundation of the methodological issues regarding the area. It discusses the methodological and epistemological positions of the leading researchers highlighted as the most productive investigators on the subject in the country. Method: The research adopts the content analysis coupled with metric studies to contextualize the indicators related to productivity, to the types of authorship and citation analysis. The bibliographic coupling method is considered an analysis mode which analyzes concomitant citations. It develops a theoretical framework about the importance of scientific production analysis in different knowledge fields. The study investigates, from a theoretical perspective, the concepts about research methodology and the complementarity between methodology and epistemology in conducting research. Results: The results of the analysis showed that the production of the highlighted authors presents the methodology as a thematic focus to be applied to IS contexts, as well as a research object in the field. The prominent productivity of the authors is justified especially by deepening the meta studies about the ways to conduct research in IS. This study also identifies a trend to single-authored studies about the theme. Conclusions: The research considers that meta studies and applied and methodological studies are important to recognize a consistent theoretical and practical core in the IS area. Regarding the epistemological influences identified by the citation analysis, the study observes that the critical rationalist epistemology and the social and political epistemology are highlighted in the construction of the theoretical framework of the most productive authors.

Introdução: Considera que a literatura na área de Ciência da Informação (CI) compreende uma diversidade temática com baixo destaque para assuntos relacionados aos modos de fazer pesquisa. Analisa a produção científica dos autores que tratam da temática metodologia de pesquisa na literatura de Ciência da Informação (CI) e o referencial no qual se fundamentam as questões metodológicas relativas à área. Discute as posições metodológicas e epistemológicas dos pesquisadores destacados como mais produtivos nacionalmente na temática. Método: Adota a modalidade de análise de conteúdo aliada aos estudos métricos para contextualizar os indicadores gerados referentes à produção, à colaboração relacionada aos tipos de autoria e à análise de citação. Considera o acoplamento bibliográfico como uma modalidade de análise em que são estudadas as citações concomitantes. Desenvolve referencial teórico sobre a importância da análise de produção científica nos domínios do conhecimento. Explora concepções teóricas sobre metodologia de pesquisa e a complementaridade desta com a epistemologia no fazer pesquisa. Resultados: Evidencia, na produção dos autores, a metodologia como foco temático aplicado a contextos da CI e também como objeto de pesquisa da referida área. Considera que a produtividade proeminente dos autores justifica-se especialmente pelo aprofundamento nos metaestudos sobre modos de fazer pesquisa em CI. Identifica a tendência aos estudos de autoria única sobre o tema. Conclusões: Considera que a realização de metaestudos e também de estudos aplicados e metodológicos é importante para que se reconheça, na área de CI, um núcleo teórico e prático consistente. Em relação às influências epistemológicas identificadas com a análise de acoplamento, observa que a epistemologia racionalista crítica e a epistemologia social e política são destacadas na construção do referencial teórico dos autores.
Keywords: Análise da produção científica; análise de citação; Acoplamento bibliográfico; Metodologia da Pesquisa Científica